APLIKASI WEB UNTUK EKSPLORASI MINAT DAN BAKAT MENGGUNAKAN METODE RMIB DENGAN PENDEKATAN RAD: WEB APPLICATION FOR EXPLORING INTERESTS AND APTITUDES USING THE RMIB METHOD WITH A RAD APPROACH - Muhammad Darwis; Wahyuningdiah TH Putri; Retno Hendrowati; Reza Arif Maulana (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Identifying interest in work is one of the important factors in choosing appropriate education and career paths. However, adolescents often do not yet have a clear understanding of occupational fields, and their interests may change along with their growth process and exposure to external information. Therefore, it is important to identify interests in skill areas and occupations from an early age so that they can choose suitable educational pathways. This study aims to develop a web-based RMIB interest and aptitude understanding application that can assist SMK PKP 1 Jakarta in exploring and providing recommendations to prospective students regarding the majors they should choose. The development of the web-based RMIB screening application applies the Rapid Application Development (RAD) method with active user participation. The main contribution of this study is the automation of the RMIB assessment process, which was previously conducted manually, thereby addressing limitations in time, human resources, and potential assessment bias. The application utilizes the Moodle framework with PHP and a MySQL database, hosted on AWS Cloud. It is designed to support simultaneous usage, making it suitable for large numbers of test participants. The RMIB interest and aptitude exploration application developed in this study has been tested using the black-box testing method, ensuring that all functions and features operate properly. n addition, user evaluation was conducted through a survey using a 1–5 Likert scale involving students and teachers. The evaluation results indicate that, on average, 72% of respondents agreed that the application is easy to use, easy to understand, quick to complete, and helpful in determining appropriate majors. These findings demonstrate that the application of RAD in developing web-based psychometric tools can improve process efficiency and achieve a good level of user acceptance.